A high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy and preparation method thereof

By introducing η-Al3La phase and Sm into die-cast magnesium alloys and optimizing interface characteristics, the problem of insufficient strength and thermal conductivity of magnesium alloys is solved, and a magnesium alloy with high strength and thermal conductivity is achieved to meet the application needs of multiple fields.

CN116254446BActive Publication Date: 2024-12-17CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310233060.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2024-12-17
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The existing die-cast magnesium alloys have shortcomings in strength and thermal conductivity, and cannot meet the new demands of the electronic 3C market, especially in the fields of new energy vehicles and 5G/6G communications, for the improvement of mechanical properties and thermal conductivity of lightweight materials.

Method used

Develop a high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy. By introducing η-Al3La phase and Sm into the alloy, a needle-like structure with semi-consistent relationship is formed, and Y and Te are added to optimize the microstructure and interface characteristics of the alloy, so as to Improve thermal conductivity and mechanical properties.

Benefits of technology

The yield strength is greater than 190MPa, tensile strength is greater than 275MPa and thermal conductivity is greater than 160W/(m·K) at room temperature, which meets the application needs of many fields and significantly improves the strength and thermal conductivity of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004121094310000011
    Figure HDA0004121094310000011
  • Figure HDA0004121094310000021
    Figure HDA0004121094310000021
  • Figure HDA0004121094310000031
    Figure HDA0004121094310000031
Patent Text Reader

Abstract

The present invention provides a die-cast rare earth magnesium alloy, wherein the die-cast rare earth magnesium alloy includes an η‑Al3La phase; the η‑Al3La phase is in a semi-coherent relationship with a matrix; the η‑Al3La phase is a needle-shaped η‑Al3La phase; the η‑Al3La phase continuously or semi-continuously forms a spatial three-dimensional structure in the eutectic region. The die-cast rare earth magnesium alloy designed by the present invention with a specific composition and microstructure can simultaneously improve the mechanical properties and thermal conductivity of the alloy. The room temperature yield strength of the high-strength and ultra-high thermal conductivity die-cast magnesium alloy provided by the present invention is greater than 190MPa, the tensile strength is greater than 275MPa, the elongation is greater than 6%, and the thermal conductivity is greater than 160W / (m·K); it is one of the alloys with the best comprehensive mechanics at room temperature and the highest thermal conductivity among the die-cast magnesium alloys reported so far.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of die-cast rare earth magnesium alloy materials, and relates to a die-cast rare earth magnesium alloy and a preparation method thereof, and in particular to a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium and magnesium alloys are the lightest metal structural materials currently in use, with a density of only 1 / 5 of steel, about 1 / 3 of titanium alloy, and 2 / 3 of aluminum alloy. Therefore, magnesium alloy is one of the most ideal weight-reducing materials currently available. More than 90% of magnesium alloy products on the market are prepared by die-casting. Currently, die-cast magnesium alloys occupy the main market in electronic 3C housings, but their application in the automotive, aerospace, rail transit and other parts markets is still very limited. The main reason is that their relative strength is not high and their functional performance is weak. In addition, with the development of the electronic 3C industry, the performance requirements for die-cast magnesium alloy housings are also increasing, requiring higher stiffness, higher thermal conductivity, etc. In terms of strength, the strength of die-cast magnesium alloys is generally around 250MPa, which is significantly lower than the 280-300MPa of die-cast aluminum alloys. In terms of thermal conductivity, the thermal conductivity of traditional die-cast AZ91D magnesium alloys is around 60W / (m·K), while the thermal conductivity of the newly developed high thermal conductivity die-cast magnesium alloys has been increased to around 110W / (m·K), but it is still significantly lower than the thermal conductivity of the second-generation high thermal conductivity aluminum alloys widely used in the market (around 160W / (m·K)). Therefore, in order to achieve the wide application of magnesium alloys in multiple fields, it is necessary to develop new die-cast magnesium alloys with both high strength and high thermal conductivity.

[0003] At present, AZ91D die-cast magnesium alloy occupies more than 80% of the market for die-cast magnesium alloys. The alloy has excellent die-casting performance, forming performance and mechanical properties. The yield strength of the alloy at room temperature is 150-160MPa, the tensile strength is 240-270MPa, and the elongation is 3-6%; however, the thermal conductivity of the alloy is poor, and the thermal conductivity coefficient is only 50-60W / (m·K). Therefore, its low yield strength and low thermal conductivity can no longer meet the new needs of the electronic 3C market. In addition, with the rapid development of new energy vehicles, 5G / 6G communications, etc., while pursuing lightweight, new requirements have been put forward for the mechanical properties and thermal conductivity of materials, such as requiring magnesium alloy materials to have a yield strength greater than 190MPa, an elongation greater than 6%, and a thermal conductivity greater than 120W / (m·K). After decades of research, researchers have developed a series of high thermal conductivity magnesium alloys, such as Mg-Zn, Mg-Mn, Mg-Zn-Ag, Mg-Ag-RE and Mg-Al-RE magnesium alloys. These alloys have higher thermal conductivity than traditional AZ91D magnesium alloys. For example, the thermal conductivity of Mg-Zn alloys can reach more than 120W / (m·K), while the thermal conductivity of Mg-Mn alloys can reach more than 140W / (m·K). However, most high thermal conductivity magnesium alloys have poor die-casting performance and severe thermal cracking tendency, and the cost of Ag-containing magnesium alloys is too high to be widely used. The newly developed high thermal conductivity die-casting magnesium alloy Mg-Al-RE alloy has good cold chamber die-casting performance, excellent mechanical properties and good thermal conductivity; however, the room temperature yield strength of the alloy is equivalent to that of AZ91D alloy, and the thermal conductivity is generally 110-120W / (m·K), which still cannot fully meet the market demand.

[0004] Therefore, in order to achieve widespread application of die-cast magnesium alloys, it is necessary to develop a more suitable new type of die-cast magnesium alloy with greatly improved strength and thermal conductivity. This is an inevitable trend in the development of die-cast magnesium alloys and one of the problems that many researchers in the industry urgently need to solve. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a die-cast rare earth magnesium alloy and a preparation method thereof, in particular, a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-cast magnesium alloy provided by the present invention has a yield strength greater than 190MPa, a tensile strength greater than 275MPa, an elongation greater than 6%, and a thermal conductivity greater than 160W / (m·K) at room temperature, and has high strength and thermal conductivity.

[0006] The present invention provides a die-cast rare earth magnesium alloy, wherein the die-cast rare earth magnesium alloy includes an η-Al3La phase;

[0007] The η-Al3La phase is in a semi-coherent relationship with the matrix;

[0008] The η-Al3La phase is a needle-shaped η-Al3La phase;

[0009] The η-Al3La phase is continuous or semi-continuous in the eutectic region to form a spatial three-dimensional structure.

[0010] Preferably, the η-Al3La phase is the second phase;

[0011] The η-Al3La phase is distributed in the eutectic region and also penetrates the grain boundary;

[0012] The η-Al3La phase is mostly distributed in the eutectic region;

[0013] A small portion of the η-Al3La phase penetrates the grain boundary;

[0014] The small portion of η-Al3La phase penetrating the grain boundary accounts for 3% to 8% of the total η-Al3La phase.

[0015] Preferably, the length of the needle-shaped η-Al3La phase is 0.05 to 6 μm;

[0016] The width of the needle-shaped η-Al3La phase is 30 to 160 nm;

[0017] The η-Al3La phase spans the grain boundary, connecting the eutectic region and the magnesium matrix of the α-Mg grains;

[0018] The die-cast rare earth magnesium alloy also has a semi-coherent η-Al3Sm / Mg interface.

[0019] The present invention provides a die-cast rare earth magnesium alloy, which comprises, by mass percentage:

[0020] Al: 3.5wt% to 6.2wt%;

[0021] La: 3wt% to 6.5wt%;

[0022] Sm: 1.5wt% to 3.5wt%;

[0023] Y: 0.1wt% to 0.5wt%;

[0024] Te: 0.03wt%~0.4wt%;

[0025] Mn: 0wt%~0.5wt%;

[0026] The balance is magnesium;

[0027] Among them, the mass ratio of (La+Sm) / Al is greater than 1.1 and less than 1.3.

[0028] Preferably, the die-cast rare earth magnesium alloy also includes impurity elements;

[0029] The total amount of impurity elements is less than 0.05wt%;

[0030] The impurity elements include one or more of Si, Fe, Ni, Cu and Be;

[0031] The die-cast rare earth magnesium alloy is a high-strength die-cast magnesium alloy;

[0032] The die-cast rare earth magnesium alloy is an ultra-high thermal conductivity die-cast magnesium alloy.

[0033] The present invention provides a method for preparing a die-cast rare earth magnesium alloy, comprising the following steps:

[0034] 1) smelting a magnesium source, an aluminum source, a lanthanum source, a samarium source, a yttrium source and a tellurium source to obtain an alloy liquid;

[0035] 2) The alloy liquid obtained in the above steps is subjected to high pressure casting to obtain a die-cast rare earth magnesium alloy.

[0036] Preferably, the magnesium source comprises magnesium;

[0037] The aluminum source includes aluminum;

[0038] The lanthanum source includes a magnesium-lanthanum master alloy;

[0039] The samarium source includes a magnesium-samarium master alloy;

[0040] The yttrium source includes a magnesium-yttrium master alloy;

[0041] The tellurium source includes a magnesium-tellurium master alloy.

[0042] Preferably, the smelting temperature is 700-730°C;

[0043] The smelting time is less than or equal to 15 hours;

[0044] The step 1) is specifically as follows:

[0045] 11) smelting the magnesium source, the lanthanum source, the samarium source and the yttrium source to obtain a first mixed metal liquid;

[0046] 12) Mixing the first mixed metal liquid obtained in the above step with a tellurium source to obtain a third mixed metal liquid;

[0047] 13) The third mixed metal liquid obtained in the above step is mixed with an aluminum source again to obtain an alloy liquid.

[0048] Preferably, the step 1) further comprises a manganese source;

[0049] The manganese source includes a magnesium-manganese master alloy;

[0050] The step 1) is specifically as follows:

[0051] 1a) smelting a magnesium source, a lanthanum source, a samarium source and a yttrium source to obtain a first mixed metal liquid;

[0052] 1b) mixing the first mixed metal liquid obtained in the above step with a manganese source to obtain a second mixed metal liquid;

[0053] 1c) mixing the second mixed metal liquid obtained in the above step with a tellurium source to obtain a third mixed metal liquid;

[0054] 1d) The third mixed metal liquid obtained in the above step is mixed with an aluminum source again to obtain an alloy liquid.

[0055] Preferably, the temperature of the alloy liquid for high pressure casting is 690-710°C;

[0056] The high pressure casting method includes cold chamber high pressure casting;

[0057] The injection pressure of the high pressure casting is 80-160 MPa;

[0058] The injection speed of the high pressure casting is 6 to 10 m / s;

[0059] The pressurization time of the high pressure casting is 12 to 18 ms;

[0060] The holding pressure of the high pressure casting is 40-70 MPa;

[0061] The holding time of the high pressure casting is 8 to 15 seconds.

[0062] The present invention provides a die-cast rare earth magnesium alloy, wherein the die-cast rare earth magnesium alloy includes an η-Al3La phase; the η-Al3La phase is in a semi-coherent relationship with a matrix; the η-Al3La phase is a needle-shaped η-Al3La phase; the η-Al3La phase continuously or semi-continuously forms a spatial three-dimensional structure in the eutectic region. Compared with the prior art, the present invention creatively designs a die-cast rare earth magnesium alloy with a specific composition and microstructure, wherein the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy contains Al and La, and after melting, a needle-shaped η-Al3La phase is formed during the solidification process, and this phase maintains a certain orientation relationship with the matrix, and effectively connects the eutectic region with the magnesium matrix of α-Mg grains across the grain boundary; the η-Al3La phase of this new structure and the interface formed with the magnesium matrix have good thermal conductivity, thereby significantly improving the thermal conductivity of the alloy. At the same time, this continuous or semi-continuous eutectic zone structure can effectively hinder grain boundary sliding, and the needle-shaped second phase can also effectively hinder dislocations, so that the alloy maintains a high strength; in addition, the semi-coherent η-Al3Sm / Mg interface can effectively coordinate the deformation of the matrix, so that the alloy has excellent plasticity. Second, the alloy also contains Sm. As a rare earth, Sm can effectively participate in the formation of Al-RE phases, such as η-Al3RE phases, but at the same time it can also significantly refine the size of the second phase, thereby significantly increasing the η-Al3Sm / Mg interface; on the one hand, it can increase the density of dislocation barriers and improve the mechanical properties of the alloy, and on the other hand, it can improve the thermal conductivity of the alloy; in addition, Sm atoms have more free electrons than La atoms, so the local electron density after the formation of the intermetallic phase is also increased, thereby increasing the thermal conductivity of the intermetallic phase. Third, the alloy also contains a small amount of Y, which can form a dense oxide film on the surface of the melt when the alloy is in the molten state, thereby significantly improving the oxidation resistance of the alloy melt, reducing the content of oxygen and other gas impurities in the melt to a certain extent, thereby improving the mechanical properties and thermal conductivity of the magnesium matrix itself; in addition, the binding force between Y and Al is significantly stronger than that between La and Sm, and the Al content in the magnesium matrix can be reduced as much as possible during the solidification process, and an Al2Y phase can be formed; the reduction of the Al content in the matrix can also improve the thermal conductivity of the magnesium matrix to a certain extent. Finally, the alloy also contains a trace amount of Te, which can significantly improve the quality of the melt and significantly reduce the gas content of the melt; in addition, trace amounts of Te tend to be distributed at the interface, which can effectively adjust the interface properties, thereby regulating the mechanical properties and thermal conductivity of the alloy; in addition, Te can significantly improve the plasticity. Therefore, the alloy provided by the present invention has extremely excellent mechanical properties and thermal conductivity.

[0063] Experimental results show that the high-strength and high-thermal-conductivity die-cast rare earth magnesium alloy provided by the present invention has a yield strength greater than 190 MPa, a tensile strength greater than 275 MPa, a tensile elongation at break greater than 6%, and a room temperature thermal conductivity greater than 160 W / (m·K). BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 The engineering stress-strain curves of the high-strength and ultra-high thermal-conductivity die-cast rare earth magnesium alloys prepared in Examples 1 to 3 of the present invention;

[0065] Figure 2 This is a back electron scattering scanning electron microscope photograph of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 1 of the present invention;

[0066] Figure 3 TEM photo 1 of the η-Al3La phase in the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 4 of the present invention;

[0067] Figure 4 TEM photo 2 of the η-Al3La phase in the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 4 of the present invention;

[0068] Figure 5 This is the SAED spectrum of the η-Al3La phase in the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0069] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0070] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0071] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably adopts analytically pure materials or materials with conventional purity requirements in the field of die-casting magnesium alloy preparation.

[0072] The brands and abbreviations of all raw materials of the present invention are conventional brands and abbreviations in the art. Each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the brands, abbreviations and corresponding uses.

[0073] The abbreviations of the processes used in the present invention are all conventional abbreviations in the field. The specific steps and conventional parameters of each abbreviation are clear and definite in its relevant field. Those skilled in the art can implement them in a conventional manner based on the abbreviations.

[0074] The present invention provides a die-cast rare earth magnesium alloy, wherein the die-cast rare earth magnesium alloy includes an η-Al3La phase;

[0075] The η-Al3La phase is in a semi-coherent relationship with the matrix;

[0076] The η-Al3La phase is a needle-shaped η-Al3La phase;

[0077] The η-Al3La phase is continuous or semi-continuous in the eutectic region to form a spatial three-dimensional structure.

[0078] In the present invention, the η-Al3La phase is the second phase.

[0079] In the present invention, the η-Al3La phase is preferably distributed in the eutectic region and also penetrates the grain boundary.

[0080] In the present invention, the η-Al3La phase is preferably mostly distributed in the eutectic region.

[0081] In the present invention, a small portion of the η-Al3La phase preferably penetrates the grain boundary.

[0082] In the present invention, the small portion of η-Al3La phase penetrating the grain boundary accounts for 3% to 8% of the total η-Al3La phase, more preferably 4% to 7%, and more preferably 5% to 6%.

[0083] In the present invention, the length of the needle-shaped η-Al3La phase is preferably 0.05 to 6 μm, more preferably 0.5 to 5 μm, and more preferably 1 to 4 μm.

[0084] In the present invention, the width of the needle-shaped η-Al3La phase is preferably 30 to 160 nm, more preferably 40 to 140 nm, more preferably 50 to 120 nm, and more preferably 60 to 100 nm.

[0085] In the present invention, the η-Al3La phase spans across the grain boundary, preferably connecting the eutectic region and the magnesium matrix of the α-Mg grains.

[0086] In the present invention, the die-cast rare earth magnesium alloy also preferably has a semi-coherent η-Al3Sm / Mg interface.

[0087] The present invention provides a die-cast rare earth magnesium alloy, which comprises, by mass percentage:

[0088] Al: 3.5wt% to 6.2wt%;

[0089] La: 3wt% to 6.5wt%;

[0090] Sm: 1.5wt% to 3.5wt%;

[0091] Y: 0.1wt% to 0.5wt%;

[0092] Te: 0.03wt%~0.4wt%;

[0093] Mn: 0wt%~0.5wt%;

[0094] The balance is magnesium;

[0095] Among them, the mass ratio of (La+Sm) / Al is greater than 1.1 and less than 1.3.

[0096] In the present invention, the added amount of Al is 3.5wt% to 6.2wt%, may be 4.0wt% to 6.0wt%, and preferably 4.5wt% to 5.5wt%.

[0097] In the present invention, the amount of La added is 3wt% to 6.5wt%, may be 3.5wt% to 6.0wt%, and preferably 4.0wt% to 5.5wt%.

[0098] In the present invention, the added amount of Sm is 1.5wt% to 3.5wt%, may be 1.9wt% to 3.1wt%, and preferably is 2.3wt% to 2.7wt%.

[0099] In the present invention, the amount of Y added is 0.1wt% to 0.5wt%, may be 0.15wt% to 0.45wt%, preferably 0.2wt% to 0.4wt%, more preferably 0.25wt% to 0.35wt%.

[0100] In the present invention, the added amount of Te is 0.03wt% to 0.4wt%, may be 0.1wt% to 0.35wt%, preferably 0.15wt% to 0.3wt%, more preferably 0.2wt% to 0.25wt%.

[0101] In the present invention, the added amount of Mn is 0wt% to 0.5wt%, may be 0.1wt% to 0.4wt%, and preferably 0.2wt% to 0.3wt%.

[0102] In the present invention, the mass ratio of (La+Sm) / Al is greater than 1.1 and less than 1.3, more preferably greater than or equal to 1.12 and less than or equal to 1.28, more preferably greater than or equal to 1.15 and less than or equal to 1.25, and more preferably greater than or equal to 1.17 and less than or equal to 1.23.

[0103] In the present invention, the die-cast rare earth magnesium alloy preferably further includes impurity elements.

[0104] In the present invention, the total amount of impurity elements is preferably less than 0.05 wt%, more preferably 0.04 wt%, and more preferably 0.03 wt%.

[0105] In the present invention, the impurity elements preferably include one or more of Si, Fe, Ni, Cu and Be, and more preferably Si, Fe, Ni, Cu or Be.

[0106] In the present invention, the die-cast rare earth magnesium alloy is preferably a high-strength die-cast magnesium alloy.

[0107] In the present invention, the die-cast rare earth magnesium alloy is preferably an ultra-high thermal conductivity die-cast magnesium alloy.

[0108] The present invention is to complete and refine the overall technical solution, better ensure the structure and composition of the die-cast rare earth magnesium alloy, and further improve the strength and thermal conductivity of the die-cast rare earth magnesium alloy. The high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy can be specifically composed of the following:

[0109] A high-strength and ultra-high thermal conductivity die-cast magnesium alloy, comprising:

[0110] 3.5-6.2wt% Al, 3-6.5wt% La, 1.5-3.5wt% Sm, 0.1-0.5wt% Y, 0.03-0.4wt% Te, 0-0.5wt% Mn, (La+Sm) / Al mass ratio is greater than 1.1 and less than 1.3, the total amount of impurity elements Si, Fe, Ni, Cu, Be, etc. is less than 0.05wt%, and the balance is magnesium.

[0111] The high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention contains Al and La. During the solidification process of the melt, the two will combine to form an η-Al3La phase that is semi-coherent with the matrix and has excellent thermal conductivity. The continuous or semi-continuous eutectic region forms a spatial three-dimensional structure, which effectively hinders grain boundary sliding. Most of the η-Al3La phase is densely distributed in the eutectic region, and another small part of the η-Al3La phase runs through the grain boundary, thereby effectively hindering the eutectic region / α-Mg interface sliding and hindering dislocation; but at the same time, phonons can be effectively transmitted with the help of η-Al3La and its interface with the matrix; therefore, the alloy exhibits excellent mechanical properties and thermal conductivity. The alloy also contains Sm, which can improve the thermal conductivity of the η-Al3RE phase and significantly refine the size of the η-Al3RE phase, thereby significantly increasing the interface of η-Al3RE / Mg, and improving the mechanical properties and thermal conductivity of the alloy; in addition, the alloy also contains a small amount of Y, which can effectively protect the alloy melt, improve the alloy quality, and can strongly combine with Al to form Al2Y phase, to a certain extent reduce the Al content in the magnesium matrix, and improve the thermal conductivity of the magnesium matrix. Finally, the alloy also contains a trace amount of Te, which can significantly reduce the gas content of the melt, regulate the mechanical properties and thermal conductivity of the alloy by adjusting the interface properties, and significantly improve the plasticity.

[0112] The high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention comprises 3.5-6.2wt% Al. In the present invention, the mass content of Al in the high-strength ultra-high thermal conductivity die-cast magnesium alloy is preferably 3.8-5.5wt%. The content of Al in the high-strength ultra-high thermal conductivity die-cast magnesium alloy provided by the present invention enables the alloy melt to have very good flow properties, thereby enabling the high-strength ultra-high thermal conductivity magnesium alloy provided by the present invention to use a die-casting method to prepare die-castings with complex structures.

[0113] The high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention includes 3 to 6.5 wt% of La. In the present invention, the mass content of La in the high-strength ultra-high thermal conductivity die-cast magnesium alloy is preferably 3 to 5 wt%. In the present invention, the La can work together with the Al described in the above technical solution to further improve the fluidity of the alloy liquid, and at the same time can also significantly improve the oxidation resistance of the alloy melt, so that the high-strength ultra-high thermal conductivity die-cast magnesium alloy provided by the present invention has better casting quality. In addition, La and Al can form η-Al3La phase during the solidification process, so that the alloy has excellent mechanical properties and thermal conductivity.

[0114] The high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention comprises 1.5-3.5wt% Sm. In the present invention, the mass content of Sm in the high-strength ultra-high thermal conductivity magnesium alloy is preferably 1.8-2.7wt%. In the present invention, the Sm can further improve the fluidity and oxidation resistance of the alloy melt, and promote the nucleation of the η-Al3RE phase during the solidification process, thereby significantly refining the η-Al3RE phase.

[0115] The high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention comprises 0.1-0.5wt% Y. In the present invention, the mass content of Y in the high-strength ultra-high thermal conductivity magnesium alloy is preferably 0.2-0.3wt%. In the present invention, Y can significantly improve the oxidation resistance of the alloy melt, and strongly combine with Al to form Al2Y during the solidification process, thereby reducing the remaining solid solution Al atoms in the magnesium matrix to a certain extent and improving the thermal conductivity of the matrix.

[0116] The high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention comprises 0.03-0.4wt% Te. In the present invention, the mass content of Te in the high-strength ultra-high thermal conductivity magnesium alloy is preferably 0.1-0.2wt%. In the present invention, the Te can significantly improve the melt quality, reduce the gas content, and tend to segregate to the interface, thereby improving the thermal conductivity of the matrix and the plasticity of the alloy.

[0117] The high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention may also contain the common alloying element Mn, but the addition of Mn will have a certain degree of adverse effect on the plasticity and thermal conductivity of the alloy.

[0118] In the present invention, the high-strength and ultra-high thermal conductivity die-cast magnesium alloy preferably includes: 3.5-6.2wt% Al, 3-6.5wt% La, 1.5-3.5wt% Sm, 0.1-0.5wt% Y, 0.03-0.4wt% Te, 0-0.5wt% Mn, (La+Sm) / Al mass ratio greater than 1.1 and less than 1.3, the total amount of impurity elements Si, Fe, Ni, Cu, Be, etc. is less than 0.05wt%, and the balance is magnesium.

[0119] The present invention provides a method for preparing a die-cast rare earth magnesium alloy, comprising the following steps:

[0120] 1) smelting a magnesium source, an aluminum source, a lanthanum source, a samarium source, a yttrium source and a tellurium source to obtain an alloy liquid;

[0121] 2) The alloy liquid obtained in the above steps is subjected to high pressure casting to obtain a die-cast rare earth magnesium alloy.

[0122] The invention firstly smelts a magnesium source, an aluminum source, a lanthanum source, a samarium source, a yttrium source and a tellurium source to obtain an alloy liquid.

[0123] In the present invention, the magnesium source preferably includes magnesium.

[0124] In the present invention, the aluminum source preferably includes aluminum.

[0125] In the present invention, the lanthanum source preferably comprises a magnesium-lanthanum master alloy.

[0126] In the present invention, the samarium source preferably comprises a magnesium-samarium master alloy.

[0127] In the present invention, the yttrium source preferably includes a magnesium-yttrium master alloy.

[0128] In the present invention, the tellurium source preferably includes a magnesium-tellurium master alloy.

[0129] In the present invention, the smelting temperature is preferably 700-730°C, more preferably 705-725°C, and even more preferably 710-720°C.

[0130] In the present invention, the smelting time is preferably less than or equal to 15 hours, more preferably less than or equal to 13 hours, and more preferably less than or equal to 11 hours.

[0131] In the present invention, the step 1) is preferably:

[0132] 11) smelting the magnesium source, the lanthanum source, the samarium source and the yttrium source to obtain a first mixed metal liquid;

[0133] 12) Mixing the first mixed metal liquid obtained in the above step with a tellurium source to obtain a third mixed metal liquid;

[0134] 13) The third mixed metal liquid obtained in the above step is mixed with an aluminum source again to obtain an alloy liquid.

[0135] The present invention firstly smelts a magnesium source, a lanthanum source, a samarium source and a yttrium source to obtain a first mixed metal liquid.

[0136] In the present invention, the step 1) preferably further comprises a manganese source.

[0137] In the present invention, the manganese source preferably includes a magnesium-manganese master alloy.

[0138] In the present invention, the first mixed metal liquid obtained in the above steps is mixed with a tellurium source to obtain a third mixed metal liquid.

[0139] In the present invention, the third mixed metal liquid obtained in the above steps is finally mixed with the aluminum source again to obtain an alloy liquid.

[0140] In the present invention, the step 1) is preferably:

[0141] 1a) smelting a magnesium source, a lanthanum source, a samarium source and a yttrium source to obtain a first mixed metal liquid;

[0142] 1b) mixing the first mixed metal liquid obtained in the above step with a manganese source to obtain a second mixed metal liquid;

[0143] 1c) mixing the second mixed metal liquid obtained in the above step with a tellurium source to obtain a third mixed metal liquid;

[0144] 1d) The third mixed metal liquid obtained in the above step is mixed with an aluminum source again to obtain an alloy liquid.

[0145] The present invention firstly smelts a magnesium source, a lanthanum source, a samarium source and a yttrium source to obtain a first mixed metal liquid.

[0146] In the present invention, the first mixed metal liquid obtained in the above steps is mixed with a manganese source to obtain a second mixed metal liquid.

[0147] The present invention then mixes the second mixed metal liquid obtained in the above steps with a tellurium source to obtain a third mixed metal liquid.

[0148] In the present invention, the third mixed metal liquid obtained in the above steps is finally mixed with the aluminum source again to obtain an alloy liquid.

[0149] Finally, the alloy liquid obtained in the above steps is subjected to high pressure casting to obtain a die-cast rare earth magnesium alloy.

[0150] In the present invention, the temperature of the alloy liquid for high pressure casting is preferably 690-710°C, more preferably 694-706°C, and even more preferably 698-702°C.

[0151] In the present invention, the high pressure casting method preferably includes cold chamber high pressure casting.

[0152] In the present invention, the injection pressure of the high pressure casting is preferably 80 to 160 MPa, more preferably 90 to 150 MPa, more preferably 100 to 140 MPa, and more preferably 110 to 130 MPa.

[0153] In the present invention, the injection speed of the high pressure casting is preferably 6 to 10 m / s, more preferably 6.5 to 9.5 m / s, more preferably 7 to 9 m / s, and more preferably 7.5 to 8.5 m / s.

[0154] In the present invention, the pressurization time of the high pressure casting is preferably 12 to 18 ms, more preferably 13 to 17 ms, and more preferably 14 to 16 ms.

[0155] In the present invention, the holding pressure of the high pressure casting is preferably 40 to 70 MPa, more preferably 45 to 65 MPa, and even more preferably 50 to 60 MPa.

[0156] In the present invention, the holding time of the high pressure casting is preferably 8 to 15 s, more preferably 9 to 14 s, more preferably 10 to 13 s, and more preferably 11 to 12 s.

[0157] The present invention is to complete and refine the overall technical solution, better ensure the structure and composition of the die-cast rare earth magnesium alloy, and further improve the strength and thermal conductivity of the die-cast rare earth magnesium alloy. The preparation method of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy may specifically include the following steps:

[0158] A method for preparing a high-strength and ultra-high thermal conductivity die-cast magnesium alloy comprises the following steps:

[0159] 1) melting a magnesium source, an aluminum source, a lanthanum source, a samarium source, a yttrium source, and a tellurium source (or a manganese source) to obtain an alloy liquid;

[0160] 2) High-pressure casting is performed on the alloy liquid to obtain a high-strength and ultra-high thermal conductivity magnesium alloy, wherein the high-strength and ultra-high thermal conductivity magnesium alloy comprises:

[0161] 3.5-6.2wt% Al, 3-6.5wt% La, 1.5-3.5wt% Sm, 0.1-0.5wt% Y, 0.03-0.4wt% Te, 0-0.5wt% Mn, (La+Sm) / Al mass ratio is greater than 1.1 and less than 1.3, the total amount of impurity elements Si, Fe, Ni, Cu, Be, etc. is less than 0.05wt%, and the balance is magnesium.

[0162] Specifically, the smelting temperature in step 1) is 700°C to 730°C.

[0163] Specifically, the melt temperature of the high pressure casting in step 1) is 690°C to 710°C.

[0164] Specifically, the step 1) is specifically as follows:

[0165] Smelting a magnesium source, a lanthanum source, a samarium source and a yttrium source to obtain a first mixed metal liquid;

[0166] The first mixed metal liquid is mixed with a manganese source to obtain a second mixed metal liquid, and if manganese is not added, there is no second mixed metal liquid;

[0167] mixing the first mixed metal liquid (or the second mixed metal liquid) with a tellurium source to obtain a third mixed metal liquid;

[0168] The third mixed metal liquid is mixed with an aluminum source to obtain an alloy liquid.

[0169] Specifically, the high pressure casting in step 2) is cold chamber high pressure casting, the injection pressure is 80-160 MPa, the injection speed is 6-10 m / s, the pressurization time is 12-18 ms, the holding pressure is 40-70 MPa, and the holding time is 8-15 s.

[0170] Specifically, in the step 2), the alloy melt produced by high pressure casting is subjected to a scraping treatment before being transferred to the runner.

[0171] Specifically, the alloy sample obtained by high pressure casting in step 2) is a plate-shaped sample, and the sample surface size is not particularly limited, and the thickness is: 0.4 to 8 mm.

[0172] Furthermore,

[0173] The present invention melts a magnesium source, an aluminum source, a lanthanum source, a samarium source, and a tellurium source (or other alloy element sources) to obtain an alloy liquid. In the present invention, the melting temperature is preferably 710°C to 730°C, and most preferably 720°C. The present invention has no special restrictions on the melting method, and the technical scheme of metal melting well known to those skilled in the art can be adopted. The present invention preferably carries out the melting under the condition of a protective gas. The present invention has no special restrictions on the type and source of the protective gas, and the protective gas used in the preparation of magnesium alloys well known to those skilled in the art can be adopted, which can be purchased from the market. In the present invention, the protective gas is preferably SF6 and CO2. In the present invention, the volume ratio of SF6 and CO2 is preferably 1: (50 to 120), and most preferably 1: 90.

[0174] The present invention preferably smelts a magnesium source, a lanthanum source, a samarium source and a yttrium source to obtain a first mixed metal liquid; mixes the first mixed metal liquid with other alloy element sources to obtain a second mixed metal liquid, then mixes the first mixed metal liquid (or the second mixed metal liquid) with a tellurium source to obtain a third mixed metal liquid, and finally alloys the third mixed metal liquid with an aluminum source to obtain an alloy liquid. The present invention has no special restrictions on the method of smelting the magnesium source, aluminum source, lanthanum source, samarium source and yttrium source, and the technical scheme of metal smelting familiar to those skilled in the art can be adopted. Before smelting the magnesium source, lanthanum source, samarium source and yttrium source, the present invention preferably preheats the magnesium source, lanthanum source, samarium source and yttrium source. In the present invention, the preheating temperature of the magnesium source, lanthanum source, samarium source and yttrium source is preferably 180°C to 400°C, more preferably 240°C to 360°C, and most preferably 300°C.

[0175] After obtaining the first mixed metal liquid, the present invention preferably mixes the first mixed metal liquid with a manganese source to obtain a second mixed metal liquid; in the present invention, the mixing temperature of the first mixed metal liquid and the manganese source is preferably 710° C. to 730° C., more preferably 720° C. to 730° C., and most preferably 725° C. In the present invention, the mixing time of the first mixed metal liquid and the manganese source is preferably 8 minutes to 15 minutes, more preferably 10 minutes to 12 minutes; if no manganese source is added, there is no second mixed metal liquid.

[0176] After obtaining the first or second mixed metal liquid, the present invention preferably mixes the first mixed metal liquid (or the second mixed metal liquid) with a tellurium source to obtain a third mixed metal liquid; in the present invention, the mixing temperature of the first mixed metal liquid (or the second mixed metal liquid) and the tellurium source is preferably 710° C. to 720° C., more preferably 710° C. to 715° C., and most preferably 710° C. In the present invention, the mixing time of the first or second mixed metal liquid and the tellurium source is preferably 8 minutes to 15 minutes, more preferably 8 minutes to 10 minutes.

[0177] After obtaining the third mixed metal liquid, the present invention preferably mixes the third mixed metal liquid with an aluminum source to obtain an alloy liquid; in the present invention, the mixing temperature of the third mixed metal liquid and the aluminum source is preferably 710° C. to 730° C., more preferably 715° C. to 725° C., and most preferably 720° C. In the present invention, the mixing time of the first or second mixed metal liquid and the tellurium source is preferably 8 minutes to 15 minutes, more preferably 8 minutes to 10 minutes.

[0178] In the present invention, the aluminum source is preferably high-purity aluminum (99.98%). In the present invention, the magnesium source is preferably high-purity magnesium (99.99%). The present invention has no special restrictions on the sources of the aluminum source and the magnesium source, and they can be purchased from the market. In the present invention, the lanthanum source is preferably a magnesium-lanthanum master alloy. In the present invention, the samarium source is preferably a magnesium-samarium master alloy. In the present invention, the yttrium source is preferably a magnesium-yttrium master alloy. In the present invention, the tellurium source is preferably a magnesium-tellurium master alloy. In the present invention, the manganese source is preferably a magnesium-manganese master alloy. In the present invention, the mass fraction of lanthanum in the magnesium-lanthanum master alloy is preferably 15 to 30wt%, more preferably 15-20wt%. In the present invention, the mass fraction of samarium in the magnesium-samarium master alloy is preferably 15 to 30wt%, more preferably 15-20wt%. In the present invention, the mass fraction of yttrium in the magnesium-yttrium master alloy is preferably 15 to 30wt%, more preferably 15-20wt%. In the present invention, the mass fraction of tellurium in the magnesium-tellurium master alloy is preferably 0.7-3wt%, more preferably 1.5-2wt%. In the present invention, the mass fraction of manganese in the magnesium-manganese master alloy is preferably 2-7wt%, more preferably 3-4wt%.

[0179] In the present invention, there is no particular limitation on the sources of the lanthanum source, samarium source, yttrium source, tellurium source and manganese source. The sources of the above types known to those skilled in the art can be used and can be purchased from the market. In an embodiment of the present invention, the lanthanum source, samarium source, yttrium source, manganese source and tellurium source are respectively magnesium-lanthanum master alloy, magnesium-samarium master alloy, magnesium-yttrium master alloy, magnesium-tellurium master alloy and magnesium-manganese master alloy provided by Changchun Institute of Applied Chemistry, Chinese Academy of Sciences.

[0180] After obtaining the alloy liquid, argon gas may be introduced into the alloy liquid for refining. In the present invention, it is preferred not to refine. In the present invention, it is preferred to let the alloy liquid stand. In the present invention, the standing time is preferably 30 minutes to 45 minutes, and the melt temperature during the standing is preferably 700-710°C.

[0181] Before smelting the magnesium source, aluminum source, lanthanum source, samarium source, yttrium source, tellurium source and manganese source, the present invention preferably preheats the magnesium source, aluminum source, lanthanum source, samarium source, yttrium source, tellurium source and manganese source. In the present invention, the preheating temperature of the magnesium source, aluminum source, lanthanum source, samarium source, yttrium source, tellurium source and manganese source is preferably 180°C to 400°C, more preferably 240°C to 360°C, and most preferably 300°C.

[0182] After obtaining the alloy liquid, the present invention uses a cold chamber die-casting machine to perform high-pressure casting on the alloy liquid to obtain a high-strength and ultra-high thermal conductivity die-cast magnesium alloy, wherein the high-strength and ultra-high thermal conductivity die-cast magnesium alloy comprises: 3.5-6.2wt% Al, 3-6.5wt% La, 1.5-3.5wt% Sm, 0.1-0.5wt% Y, 0.03-0.4wt% Te, 0-0.5wt% Mn, (La+Sm) / Al mass ratio is greater than 1.1 and less than 1.3, the total amount of impurity elements Si, Fe, Ni, Cu, Be, etc. is less than 0.05wt%, and the balance is magnesium.

[0183] In the present invention, the die casting melt temperature is preferably 690°C to 730°C, more preferably 695°C to 715°C, and most preferably 695°C to 705°C. In the present invention, the die casting is cold chamber high pressure casting, and the parameters are set as follows: injection pressure: 80-160MPa, injection speed: 6-10m / s, pressurization time: 12-18ms, holding pressure 40-70MPa, and holding time 8-15s.

[0184] In the present invention, during high-pressure casting, the alloy melt is scraped before being transferred to the runner. The alloy sample for high-pressure casting is a plate-shaped sample with a sample surface size of 60 mm×120 mm and a thickness of 0.4 mm, 3 mm or 8 mm. Other die-casting parameters and conditions can be adopted from the technical solutions for magnesium alloy die-casting well known to those skilled in the art to ensure the quality and yield of the die-casting samples.

[0185] In the present invention, the preheating temperature of the die-casting mold is preferably 180-300°C, more preferably 220°C to 270°C, and most preferably 240°C to 260°C.

[0186] In the present invention, the high-strength and ultra-high thermal conductivity die-cast magnesium alloy includes 3.5-6.2wt% Al, 3-6.5wt% La, 1.5-3.5wt% Sm, 0.1-0.5wt% Y, 0.03-0.4wt% Te, 0-0.5wt% Mn, (La+Sm) / Al mass ratio is greater than 1.1 and less than 1.3, the total amount of impurity elements Si, Fe, Ni, Cu, Be, etc. is less than 0.05wt%, and the balance is magnesium.

[0187] The present invention can control the dosage of the magnesium source, aluminum source, lanthanum source, yttrium source, tellurium source (and manganese source) described in the above technical solution to obtain a high-strength and ultra-high thermal conductivity die-cast magnesium alloy of the above composition.

[0188] The above content of the present invention provides a high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy and its preparation method. The die-cast rare earth magnesium alloy designed by the present invention with a specific composition and microstructure is a high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy. The magnesium alloy contains Al and La. After melting, a needle-shaped η-Al3La phase will be formed during the solidification process. This phase maintains a certain orientation relationship with the matrix and effectively connects the eutectic region and the α-Mg grain magnesium matrix across the grain boundary; this new structure of η-Al3La phase and the interface formed with the magnesium matrix have good thermal conductivity, thereby significantly improving the thermal conductivity of the alloy. At the same time, this continuous or semi-continuous eutectic region structure can effectively hinder grain boundary sliding, and the needle-shaped second phase can also effectively hinder dislocations, thereby maintaining a high strength of the alloy; in addition, the semi-coherent η-Al3Sm / Mg interface can effectively coordinate the deformation of the matrix, thereby making the alloy have excellent plasticity. Second, the alloy also contains Sm. As a rare earth, Sm can effectively participate in the formation of Al-RE phase, such as η-Al3RE phase, but it can also significantly refine the size of the second phase, thereby significantly increasing the interface of η-Al3Sm / Mg; on the one hand, it can increase the density of dislocation barriers and improve the mechanical properties of the alloy, and on the other hand, it can improve the thermal conductivity of the alloy; in addition, Sm atoms have more free electrons than La atoms, so the local electron density after the formation of the intermetallic phase is also increased, which also increases the thermal conductivity of the intermetallic phase. Third, the alloy also contains a small amount of Y. When Y is in the alloy melt state, it can form a dense oxide film on the surface of the melt, thereby significantly improving the oxidation resistance of the alloy melt, and to a certain extent reducing the content of oxygen and other gas impurities in the melt, thereby improving the mechanical properties and thermal conductivity of the magnesium matrix itself; in addition, the binding force between Y and Al is significantly stronger than that between La and Sm, and the Al content in the magnesium matrix can be reduced as much as possible during the solidification process, and the Al2Y phase can be formed; the reduction of the Al content in the matrix can also improve the thermal conductivity of the magnesium matrix to a certain extent. Finally, the alloy also contains a trace amount of Te, which can significantly improve the quality of the melt and significantly reduce the gas content of the melt; in addition, the trace amount of Te tends to be distributed at the interface, which can effectively adjust the interface properties, thereby regulating the mechanical properties and thermal conductivity of the alloy; in addition, Te can significantly improve the plasticity. Therefore, the alloy provided by the present invention has extremely excellent mechanical properties and thermal conductivity.

[0189] The high-strength and ultra-high thermal conductivity die-cast magnesium alloy provided by the present invention is tested for its mechanical properties at room temperature according to the standard of GB / T 228.1-2010 "Metallic Material Uniaxial Tensile Test Method". The experimental results show that the tensile yield strength at room temperature is greater than 190MPa, the tensile strength is greater than 275MPa, and the tensile elongation at break is greater than 6%; according to the standard of ASTM-E1461 "Metallic Material Thermal Conductivity Test", the thermal conductivity at room temperature is tested, and the room temperature thermal conductivity is greater than 160W / (m·K).

[0190] In order to further illustrate the present invention, a die-cast rare earth magnesium alloy and a preparation method thereof provided by the present invention are described in detail below in combination with embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following embodiments.

[0191] The raw materials used in the following embodiments of the present invention are all commercially available products, the magnesium used is high-purity magnesium, the aluminum used is high-purity aluminum, the mass fraction of lanthanum in the magnesium-lanthanum master alloy used is 20wt%, the mass fraction of samarium in the magnesium-samarium master alloy used is 20wt%, the mass fraction of yttrium in the magnesium-yttrium master alloy used is 20wt%, the mass fraction of manganese in the magnesium-manganese master alloy used is 4wt%, and the mass fraction of tellurium in the magnesium-tellurium master alloy used is 1.5wt%.

[0192] Example 1

[0193] Preheat 19225 g of high-purity magnesium, 1200 g of high-purity aluminum, 4800 g of magnesium-lanthanum master alloy, 2400 g of magnesium-samarium master alloy, 375 g of magnesium-yttrium master alloy, and 2000 g of magnesium-tellurium master alloy to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing; then, when the melt is heated to 720°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing to obtain an alloy liquid; the alloy liquid is cooled to 695-700°C and allowed to stand for 30 minutes.

[0194] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 695-700°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 120MPa, the injection speed is 8m / s, the pressurization time is 13ms, the holding pressure is 60MPa, and the holding time is 8s.

[0195] The composition of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 1 of the present invention was detected by inductively coupled plasma emission spectrometry.

[0196] The test results show that the high-strength and ultra-high thermal conductive magnesium alloy obtained in Example 1 of the present invention includes: 3.92wt% Al, 3.11wt% La, 1.55wt% Sm, 0.23wt% Y, 0.09wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.02wt%, and the balance is magnesium.

[0197] The high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 1 of the present invention was subjected to mechanical property tests and scanning photo observations. The results are as follows: Figure 1 and Figure 2 shown.

[0198] See also Figure 1 , Figure 1 Engineering stress-strain curves of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloys prepared in Examples 1 to 3 of the present invention.

[0199] See also Figure 2 , Figure 2 This is a back electron scattering scanning electron microscope photograph of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 1 of the present invention.

[0200] Depend on Figure 1 and Figure 2 It can be seen that the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 1 of the present invention has excellent mechanical properties, fine and uniform structure, and the second phase is finer than that of traditional Mg-Al-RE alloys.

[0201] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0202] The experimental results show that at room temperature, the yield strength is 198±3MPa, the tensile strength is 287±7MPa, and the elongation at break is 7.2±0.5%.

[0203] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity was tested. The experimental results showed that the thermal conductivity at room temperature was 171±3W / (m·K).

[0204] Example 2

[0205] Preheat 19900 g of high-purity magnesium, 1050 g of high-purity aluminum, 4500 g of magnesium-lanthanum master alloy, 2250 g of magnesium-samarium master alloy, 300 g of magnesium-yttrium master alloy, and 2000 g of magnesium-tellurium master alloy to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring and mixed for 8 minutes; then, when the melt is heated to 720°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring and mixed for 8 minutes to obtain an alloy liquid; the alloy liquid is cooled to 695-700°C and allowed to stand for 45 minutes.

[0206] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 695-700°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 160MPa, the injection speed is 10m / s, the pressurization time is 18ms, the holding pressure is 70MPa, and the holding time is 8s.

[0207] The composition of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 2 of the present invention was detected by inductively coupled plasma emission spectrometry.

[0208] The test results show that the high-strength and ultra-high thermal conductive magnesium alloy obtained in Example 2 of the present invention includes: 3.45wt% Al, 3.01wt% La, 1.44wt% Sm, 0.18wt% Y, 0.09wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0209] The high-strength ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 2 of the present invention was tested for mechanical properties (such as Figure 1 as shown) and scanned photographs for observation.

[0210] It can be seen that the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 2 of the present invention has excellent mechanical properties.

[0211] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0212] The experimental results show that at room temperature, the yield strength is 193±3MPa, the tensile strength is 278±3MPa, and the elongation at break is 8.1±0.8%.

[0213] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0214] The experimental results show that the thermal conductivity is 164±3W / (m·K) at room temperature.

[0215] Example 3

[0216] 14740 g of high-purity magnesium, 1860 g of high-purity aluminum, 7500 g of magnesium-lanthanum master alloy, 3600 g of magnesium-samarium master alloy, 300 g of magnesium-yttrium master alloy, and 2000 g of magnesium-tellurium master alloy were preheated to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing; then, when the melt is heated to 730°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing to obtain an alloy liquid; the alloy liquid is cooled to 700-705°C and allowed to stand for 30 minutes.

[0217] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 700-705°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 80MPa, the injection speed is 6m / s, the pressurization time is 12ms, the holding pressure is 50MPa, and the holding time is 10s.

[0218] The composition of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 3 of the present invention was detected by inductively coupled plasma emission spectrometry.

[0219] The test results show that the high-strength and ultra-high thermal conductive magnesium alloy obtained in Example 3 of the present invention includes: 6.18wt% Al, 5.01wt% La, 2.37wt% Sm, 0.19wt% Y, 0.09wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0220] The high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 3 of the present invention was tested for mechanical properties. The results are as follows: Figure 1It can be seen that the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 3 of the present invention has excellent mechanical properties.

[0221] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0222] The experimental results show that at room temperature, the yield strength is 202±4MPa, the tensile strength is 283±6MPa, and the elongation at break is 6.8±0.7%.

[0223] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0224] The experimental results show that the thermal conductivity is 170±4W / (m·K) at room temperature.

[0225] Example 4

[0226] Preheat 15390 g of high-purity magnesium, 1860 g of high-purity aluminum, 9750 g of magnesium-lanthanum master alloy, 2250 g of magnesium-samarium master alloy, 150 g of magnesium-yttrium master alloy, and 600 g of magnesium-tellurium master alloy to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing; then, when the melt is heated to 730°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing to obtain an alloy liquid; the alloy liquid is cooled to 700-705°C and allowed to stand for 45 minutes.

[0227] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 700-705°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 120MPa, the injection speed is 8m / s, the pressurization time is 15ms, the holding pressure is 60MPa, and the holding time is 10s.

[0228] The composition of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 4 of the present invention was detected by inductively coupled plasma emission spectrometry.

[0229] The test results show that the high-strength and ultra-high thermal conductive magnesium alloy obtained in Example 4 of the present invention includes: 6.14wt% Al, 6.38wt% La, 1.46wt% Sm, 0.08wt% Y, 0.03wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0230] The high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 4 of the present invention was characterized.

[0231] See also Figure 3 , Figure 3 TEM Photo 1 of the η-Al3La phase in the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 4 of the present invention.

[0232] See also Figure 4 , Figure 4 TEM Photo 2 of the η-Al3La phase in the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 4 of the present invention.

[0233] Depend on Figure 3 and 4 It can be seen that the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared by the present invention has a uniform and refined needle-shaped η-Al3RE phase.

[0234] See also Figure 5 , Figure 5 This is the SAED spectrum of the η-Al3La phase in the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared in Example 4 of the present invention.

[0235] Depend on Figure 5 It can be seen that there is a definite orientation relationship between the η-Al3La phase and the Mg matrix in the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy prepared by the present invention.

[0236] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0237] The experimental results show that at room temperature, the yield strength is 199±5MPa, the tensile strength is 280±5MPa, and the elongation at break is 7.0±0.9%.

[0238] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0239] The experimental results show that the thermal conductivity is 165±3W / (m·K) at room temperature.

[0240] Example 5

[0241] 11390g of high purity magnesium, 1860g of high purity aluminum, 6750g of magnesium lanthanum master alloy, 5250g of magnesium samarium master alloy, 750g of magnesium yttrium master alloy, and 4000g of magnesium tellurium master alloy were preheated to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing; then, when the melt is heated to 730°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing to obtain an alloy liquid; the alloy liquid is cooled to 700-705°C and allowed to stand for 45 minutes.

[0242] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 700-705°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 130MPa, the injection speed is 9m / s, the pressurization time is 15ms, the holding pressure is 60MPa, and the holding time is 12s.

[0243] The composition of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 5 of the present invention was detected by inductively coupled plasma emission spectrometry.

[0244] The test results show that the high-strength and ultra-high thermal conductive magnesium alloy obtained in Example 5 of the present invention includes: 6.11wt% Al, 4.46wt% La, 3.48wt% Sm, 0.47wt% Y, 0.19wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0245] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0246] The experimental results show that at room temperature, the yield strength is 201±5MPa, the tensile strength is 282±6MPa, and the elongation at break is 6.6±0.6%.

[0247] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0248] The experimental results show that the thermal conductivity is 166±3W / (m·K) at room temperature.

[0249] Example 6

[0250] 13300 g of high purity magnesium, 1200 g of high purity aluminum, 4800 g of magnesium lanthanum master alloy, 2400 g of magnesium samarium master alloy, 300 g of magnesium yttrium master alloy, and 8000 g of magnesium tellurium master alloy were preheated to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring and mixed for 8 minutes; then, when the melt is heated to 720°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring and mixed for 8 minutes to obtain an alloy liquid; the alloy liquid is cooled to 695-700°C and allowed to stand for 45 minutes.

[0251] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 695-700°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 120MPa, the injection speed is 10m / s, the pressurization time is 15ms, the holding pressure is 60MPa, and the holding time is 10s.

[0252] The composition of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 6 of the present invention was detected by inductively coupled plasma emission spectrometry.

[0253] The test results show that the high-strength and ultra-high thermal conductive magnesium alloy obtained in Example 6 of the present invention includes: 3.97wt% Al, 3.16wt% La, 1.52wt% Sm, 0.16wt% Y, 0.37wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.02wt%, and the balance is magnesium.

[0254] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0255] The experimental results show that at room temperature, the yield strength is 194±3MPa, the tensile strength is 282±6MPa, and the elongation at break is 9.0±1.3%.

[0256] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0257] The experimental results show that the thermal conductivity is 176±5W / (m·K) at room temperature.

[0258] Example 7

[0259] Preheat 16950g of high-purity magnesium, 1200g of high-purity aluminum, 4800g of magnesium-lanthanum master alloy, 2400g of magnesium-samarium master alloy, 300g of magnesium-yttrium master alloy, 600g of magnesium-tellurium master alloy, and 3750g of magnesium-manganese master alloy to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the materials are melted, the melt is heated to 730°C, and then the magnesium-manganese master alloy preheated to 300°C is added to the crucible under stirring for 8 minutes; the melt is cooled to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring for 8 minutes; then the melt is heated to 720°C, and the high-purity aluminum preheated to 300°C is added to the crucible under stirring for 8 minutes to obtain an alloy liquid; the alloy liquid is cooled to 695-700°C and allowed to stand for 30 minutes.

[0260] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 695-700°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 140MPa, the injection speed is 9m / s, the pressurization time is 16ms, the holding pressure is 60MPa, and the holding time is 8s.

[0261] The composition of the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy obtained in Example 7 of the present invention was detected by inductively coupled plasma emission spectrometry.

[0262] The test results show that the high-strength and ultra-high thermal conductive magnesium alloy obtained in Example 7 of the present invention includes: 3.95wt% Al, 3.14wt% La, 1.49wt% Sm, 0.15wt% Y, 0.03wt% Te, 0.42wt% Mn, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0263] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0264] The experimental results show that at room temperature, the yield strength is 194±4MPa, the tensile strength is 282±7MPa, and the elongation at break is 7.6±0.8%.

[0265] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0266] The experimental results show that the thermal conductivity is 163±3W / (m·K) at room temperature.

[0267] Comparative Example 1

[0268] Preheat 19750 g of high-purity magnesium, 1350 g of high-purity aluminum, 4500 g of magnesium-lanthanum master alloy, 2250 g of magnesium-samarium master alloy, 150 g of magnesium-yttrium master alloy, and 2000 g of magnesium-tellurium master alloy to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing; then, when the melt is heated to 720°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing to obtain an alloy liquid; the alloy liquid is cooled to 695-700°C and allowed to stand for 30 minutes.

[0269] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 695-700°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 150MPa, the injection speed is 9m / s, the pressurization time is 115ms, the holding pressure is 60MPa, and the holding time is 10s.

[0270] The composition of the die-cast rare earth magnesium alloy obtained in Comparative Example 1 of the present invention was detected by using an inductively coupled plasma emission spectrometer.

[0271] The test results show that the magnesium alloy obtained in Comparative Example 1 of the present invention includes: 4.43wt% Al, 2.95wt% La, 1.44wt% Sm, 0.07wt% Y, 0.09wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0272] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0273] The experimental results show that at room temperature, the yield strength is 176±3MPa, the tensile strength is 272±5MPa, and the elongation at break is 11.2±1.6%.

[0274] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0275] The experimental results show that the thermal conductivity is 132±3W / (m·K) at room temperature.

[0276] Comparative Example 2

[0277] 13900 g of high purity magnesium, 1050 g of high purity aluminum, 7500 g of magnesium lanthanum master alloy, 5250 g of magnesium samarium master alloy, 300 g of magnesium yttrium master alloy, and 2000 g of magnesium tellurium master alloy were preheated to 300°C. First, preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring and mixed for 8 minutes; then, when the melt is heated to 720°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring and mixed for 8 minutes to obtain an alloy liquid; the alloy liquid is cooled to 695-700°C and allowed to stand for 45 minutes.

[0278] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 695-700°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 120MPa, the injection speed is 8m / s, the pressurization time is 15ms, the holding pressure is 60MPa, and the holding time is 15s.

[0279] The composition of the die-cast rare earth magnesium alloy obtained in Comparative Example 2 of the present invention was detected by using an inductively coupled plasma emission spectrometer.

[0280] The test results show that the magnesium alloy obtained in Comparative Example 2 of the present invention includes: 3.42wt% Al, 4.89wt% La, 3.41wt% Sm, 0.17wt% Y, 0.09wt% Te, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0281] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0282] The experimental results show that at room temperature, the yield strength is 202±5MPa, the tensile strength is 251±9MPa, and the elongation at break is 4.7±0.8%.

[0283] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0284] The experimental results show that the thermal conductivity is 112±4W / (m·K) at room temperature.

[0285] Comparative Example 3

[0286] 20550g of high-purity magnesium, 1200g of high-purity aluminum, 6000g of magnesium-lanthanum master alloy, and 2250g of magnesium-manganese master alloy are preheated to 300°C. First, the preheated high-purity magnesium and magnesium-lanthanum master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 730°C, and then the magnesium-manganese master alloy preheated to 300°C is added to the crucible under stirring for 8 minutes to obtain an alloy liquid; the alloy liquid is cooled to 700-705°C and allowed to stand for 45 minutes.

[0287] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 700-705°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 130MPa, the injection speed is 9m / s, the pressurization time is 16ms, the holding pressure is 70MPa, and the holding time is 12s.

[0288] The composition of the die-cast rare earth magnesium alloy obtained in Comparative Example 3 of the present invention was detected by using an inductively coupled plasma emission spectrometer.

[0289] The test results show that the magnesium alloy obtained in Comparative Example 3 of the present invention includes: 3.97wt% Al, 3.92wt% La, 0.24wt% Mn, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0290] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0291] The experimental results show that at room temperature, the yield strength is 165±4MPa, the tensile strength is 257±5MPa, and the elongation at break is 12.1±1.7%.

[0292] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0293] The experimental results show that the thermal conductivity is 119±4W / (m·K) at room temperature.

[0294] Comparative Example 4

[0295] 19050g of high-purity magnesium, 1200g of high-purity aluminum, 4500g of magnesium-lanthanum master alloy, 3000g of magnesium-samarium master alloy, and 2250g of magnesium-manganese master alloy are preheated to 300°C. First, the preheated high-purity magnesium, magnesium-lanthanum master alloy, magnesium-samarium master alloy, and magnesium-yttrium master alloy are placed in a crucible preheated to 300°C, and a mixed gas of SF6 and CO2 with a volume ratio of 1:90 is introduced into the crucible. After the material is melted, the melt is heated to 710°C, and then the magnesium-tellurium master alloy preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing; then, when the melt is heated to 720°C, the high-purity aluminum preheated to 300°C is added to the crucible under stirring conditions for 8 minutes of mixing to obtain an alloy liquid; the alloy liquid is cooled to 695-700°C and allowed to stand for 40 minutes.

[0296] The alloy liquid after standing is die-cast on a cold chamber die-casting machine with a clamping force of 275 tons to obtain a high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy. The die-casting temperature is 695-700°C, the die-casting mold temperature is 240±20°C, the die-casting injection pressure is 130MPa, the injection speed is 8m / s, the pressurization time is 12ms, the holding pressure is 60MPa, and the holding time is 8s.

[0297] The composition of the die-cast rare earth magnesium alloy obtained in Comparative Example 4 of the present invention was detected by using an inductively coupled plasma emission spectrometer.

[0298] The test results show that the magnesium alloy obtained in Comparative Example 4 of the present invention includes: 3.99wt% Al, 2.96wt% La, 1.92wt% Sm, 0.23wt% Mn, the total amount of impurity elements Fe, Cu, Si and Ni is less than 0.03wt%, and the balance is magnesium.

[0299] According to the standard GB / T 228.1-2010 “Uniaxial Tensile Test Method for Metallic Materials”, the room temperature mechanical properties of the alloy were tested.

[0300] The experimental results show that at room temperature, the yield strength is 170±3MPa, the tensile strength is 266±7MPa, and the elongation at break is 11.2±1.1%.

[0301] According to the standard of ASTM-E1461 "Thermal conductivity of metal materials", its room temperature thermal conductivity is tested.

[0302] The experimental results show that the thermal conductivity is 126±5W / (m·K) at room temperature.

[0303] It can be seen from the above embodiments and comparative examples that the high-strength and ultra-high thermal conductivity die-cast rare earth magnesium alloy provided by the present invention contains Al and La. During the solidification process of the melt, the two will combine to form an η-Al3La phase that is semi-coherent with the matrix and has excellent thermal conductivity. The continuous or semi-continuous eutectic region forms a spatial three-dimensional structure, which effectively hinders grain boundary sliding, and most of the η-Al3La phase is densely distributed in the eutectic region, and another small part of the η-Al3La phase runs through the grain boundary, thereby effectively hindering the eutectic region / α-Mg interface slip and hindering dislocation; but at the same time, phonons can be effectively transmitted with the help of η-Al3La and its interface with the matrix; therefore, the alloy exhibits excellent mechanical properties and thermal conductivity. The alloy also contains Sm, which can improve the thermal conductivity of the η-Al3RE phase and significantly refine the size of the η-Al3RE phase, thereby significantly increasing the interface of η-Al3RE / Mg, and improving the mechanical properties and thermal conductivity of the alloy; in addition, the alloy also contains a small amount of Y, which can effectively protect the alloy melt, improve the alloy quality, and can strongly combine with Al to form Al2Y phase, to a certain extent reduce the Al content in the magnesium matrix, and improve the thermal conductivity of the magnesium matrix. Finally, the alloy also contains a trace amount of Te, which can significantly reduce the gas content of the melt, regulate the mechanical properties and thermal conductivity of the alloy by adjusting the interface properties, and significantly improve the plasticity.

[0304] Therefore, the alloy provided by the present invention has extremely excellent mechanical properties and thermal conductivity.

[0305] The above is a detailed introduction to a high-strength, ultra-high thermal conductivity die-cast rare earth magnesium alloy and its preparation method provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A die-cast rare earth magnesium alloy, characterized in that: The die-cast rare earth magnesium alloy includes an η-Al3La phase; The η-Al3La phase is in a semi-coherent relationship with the matrix; The η-Al3La phase is a needle-shaped η-Al3La phase; The η-Al3La phase is continuous or semi-continuous in the eutectic region to form a spatial three-dimensional structure; The die-cast rare earth magnesium alloy comprises, by mass percentage: Al: 3.5wt% to 6.2wt%; La: 3wt% to 6.5wt%; Sm: 1.5wt% to 3.5wt%; Y: 0.1wt% to 0.5wt%; Te: 0.03wt%~0.4wt%; Mn: 0wt%~0.5wt%; The balance is magnesium; Among them, the mass ratio of (La+Sm) / Al is greater than 1.1 and less than 1.

3.

2. The die-cast rare earth magnesium alloy according to claim 1, characterized in that: The η-Al3La phase is the second phase; The η-Al3La phase is distributed in the eutectic region and also penetrates the grain boundary; The η-Al3La phase is mostly distributed in the eutectic region; A small portion of the η-Al3La phase penetrates the grain boundary; The small portion of η-Al3La phase penetrating the grain boundary accounts for 3% to 8% of the total η-Al3La phase.

3. The die-cast rare earth magnesium alloy according to claim 1, characterized in that: The length of the needle-shaped η-Al3La phase is 0.05 to 6 μm; The width of the needle-shaped η-Al3La phase is 30 to 160 nm.

4. The die-cast rare earth magnesium alloy according to claim 1, characterized in that: The η-Al3La phase spans the grain boundary, connecting the eutectic region and the magnesium matrix of the α-Mg grains; The die-cast rare earth magnesium alloy also has a semi-coherent η-Al3Sm / Mg interface.

5. The die-cast rare earth magnesium alloy according to claim 1, characterized in that: The die-cast rare earth magnesium alloy also includes impurity elements; The total amount of impurity elements is less than 0.05wt%; The impurity elements include one or more of Si, Fe, Ni, Cu and Be.

6. A method for preparing a die-cast rare earth magnesium alloy according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) smelting a magnesium source, an aluminum source, a lanthanum source, a samarium source, a yttrium source and a tellurium source to obtain an alloy liquid; 2) The alloy liquid obtained in the above steps is subjected to high pressure casting to obtain a die-cast rare earth magnesium alloy.

7. The preparation method according to claim 6, characterized in that: The magnesium source includes magnesium; The aluminum source includes aluminum; The lanthanum source includes a magnesium-lanthanum master alloy; The samarium source includes a magnesium-samarium master alloy; The yttrium source includes a magnesium-yttrium master alloy; The tellurium source includes a magnesium-tellurium master alloy.

8. The preparation method according to claim 6, characterized in that: The smelting temperature is 700-730°C; The smelting time is less than or equal to 15 hours; The step 1) is specifically as follows: 11) smelting the magnesium source, the lanthanum source, the samarium source and the yttrium source to obtain a first mixed metal liquid; 12) Mixing the first mixed metal liquid obtained in the above step with a tellurium source to obtain a third mixed metal liquid; 13) The third mixed metal liquid obtained in the above step is mixed with an aluminum source again to obtain an alloy liquid.

9. The preparation method according to claim 6, characterized in that: The step 1) also includes a manganese source; The manganese source includes a magnesium-manganese master alloy; The step 1) is specifically as follows: 1a) smelting a magnesium source, a lanthanum source, a samarium source and a yttrium source to obtain a first mixed metal liquid; 1b) mixing the first mixed metal liquid obtained in the above step with a manganese source to obtain a second mixed metal liquid; 1c) mixing the second mixed metal liquid obtained in the above step with a tellurium source to obtain a third mixed metal liquid; 1d) The third mixed metal liquid obtained in the above step is mixed with an aluminum source again to obtain an alloy liquid.

10. The preparation method according to claim 9, characterized in that: The temperature of the alloy liquid for high pressure casting is 690-710°C; The high pressure casting method includes cold chamber high pressure casting; The injection pressure of the high pressure casting is 80-160 MPa; The injection speed of the high pressure casting is 6 to 10 m / s; The pressurization time of the high pressure casting is 12 to 18 ms; The holding pressure of the high pressure casting is 40-70 MPa; The holding time of the high pressure casting is 8 to 15 seconds.